Polish-Romanian conferences in Suceava - Nowak, Krzysztof (Balcanica Posnaniensia. Acta et studia, 2018)
From 1999 Polish and Romanian humanists face each other on conferences in Suceava (Romanian Bucovina) which are part of “Polish Days” in Romania organized by the Association of Poles in Romania. Polish and Romanian historians, ethnographers, sociologists, politologists and linguists deliver lectures and discuss Polish-Romanian contacts and relations in the past and present. from the Polish part many historical lectures concern the interwar period and the problem of Polish refugees in Romania during the World War II. In the period between1918–1945 the relations between Poles and Romanians were rather friendly and now these topics are discussed most frequently. Among the Romanian historians there are more specialists on the relations between Moldova and the Polish Kingdom till the end of 18th century. Many historians focus on the Polish-Romanian relations in the years 1945–1989. Most of the lectures concerning the political present were delivered by the Poles. Cultural sections of the conference concentrate on mutual language influences, Polish–Romanian literature contacts, translations of Polish literature into Romania and Romanian literature into Poland, the analyses of literary works, Polish studies in Romania and Romanian studies in Poland, the perception of Romanian culture among the Poles and vice versa, the problems of religions, education, libraries, music and tourism. Polish etnographers concentrate on the problems of Polish Bucovinians but the most discussed subject is not the history of Polish Bucovinians but their local dialect. Most of the conference lectures were printed. “Polish Days” in Suceava are the most important event organized by the very active Association of Poles in Romania and they help breaking the stereotypes and enhance the integration between the Poles and Romanians.. In general the conferences in Suceava do not have their equivalent in the contacts between humanists of other countries.